Advancement of Baduy Muslims (Historical Overview of Religious Conversion in The Baduy Community) - Arif, Muhamad; Solihin, Solihin; Fatimah, Siti (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2023)
Many people think that the Baduy people are very fanatical in carrying out their customary system and at the same time rejecting outside influences, including Islam. However, researchers found different evidence of this assumption. This study aims to provide a historical overview of the connectedness of the Baduy people to the Islamic religion, so that some Baduy residents in Kampung Landeuh have now converted their religion to Islam. By using historical research methods, researchers collect sources, criticize sources, interpret information, then write about the progress of Baduy Muslims. This research resulted in three important findings. First, the Baduy people have known Islam since the beginning of the spread of Islam in Banten, when Prabu Pucuk Umun and his retainers were still living in Banten, before handing over the power of Banten to Maulana Hasanuddin. Second, there was a gradual transfer of the beliefs of the Baduy people from Sunda Wiwitan to the Agama Selam Sunda Wiwitan during the time of Maulana Yusuf, until now some Baduy people have embraced Islam. Third, there has been an increase in the number of Muslim Baduy because more and more Baduy people have left their traditional environment to live in Kampung Landeuh.Banyak orang beranggapan bahwa masyarakat Baduy sangat fanatik dalam menjalankan sistem adat sekaligus menolak keras pengaruh luar, termasuk Islam. Namun, peneliti menemukan bukti yang berbeda dari anggapan tersebut. Kajian ini bertujuan untuk memberikan gambaran sejarah tentang keterhubungan masyarakat Baduy dengan agama Islam, sehingga beberapa warga Baduy di Kampung Landeuh saat ini telah mengkonversi agama mereka sebagai penganut Islam. Dengan menggunakan metode penelitian sejarah, peneliti mengumpulkan sumber, mengkritisi sumber, menafsirkan informasi, kemudian menulis tentang kemajuan Muslim Baduy. Penelitian ini menghasilkan tiga temuan penting. Pertama, masyarakat Baduy telah mengenal Islam sejak awal penyebaran Islam di Banten, ketika Prabu Pucuk Umun dan para punggawanya masih bermukim di Banten, sebelum menyerahkan kekuasaan Banten kepada Maulana Hasanuddin. Kedua, terjadi perpindahan kepercayaan masyarakat Baduy secara bertahap dari Sunda Wiwitan menjadi Agama Selam Sunda Wiwitan pada masa Maulana Yusuf, hingga saat ini beberapa warga Baduy telah menganut Islam. Ketiga, terjadi peningkatan jumlah Baduy Muslim karena semakin banyak masyarakat Baduy yang meninggalkan lingkungan adatnya untuk tinggal di Kampung Landeuh.